The effect of prenatal and postnatal caffeine exposure on pentylentetrazole induced seizures in the non-epileptic and epileptic offsprings - (:unkn) unknown (ELSEVIER IRELAND LTD, 2019)
Caffeine, a central nervous system stimulant, has been reported to modulate seizure activity in various studies. In this study the effects of caffeine exposure on the pentylenetetrazole (PTZ) induced seizure thresholds and seizure stages in the Wistar and genetic absence epilepsy model offsprings were examined. Adult female and male Wistar rats and genetic absence epilepsy rats from Strasbourg (GAERS) consumed caffeine dissolved in water (0.3 g/L) before conception, during the gestational periods and lactation period whereas control groups of each strain received tap water. All offsprings at postnatal day 30 (PN30) subjected to 70 mg/kg of PTZ were evaluated in terms of overall seizure stages, the latency to the first generalized seizure and the c-Fos protein activity in the brain regions of somatosensorial cortex (SSCx), reticular thalamic nucleus (Rt), ventrobasal thalamus (VB), centromedial nucleus (CM) and lateral geniculate nucleus (LGN). The Wistar caffeine group had significantly shorter latency to the first generalized seizure (1.53 +/- 0.49 min) comparing to the Wistar control offsprings (3.40 +/- 0.68 min). GAERS caffeine group (6.52 +/- 2.48 min) showed significantly longer latency comparing to Wistar caffeine group (1.53 +/- 0.49 min). Although statistically not significant, GAERS caffeine group showed a longer latency comparing to the GAERS control group (4.71 +/- 1.82 min). In all regions of SSCx, Rt, VB, CM and LGN, GAERS caffeine group had lower c-Fos protein expression comparing to the GAERS control group (p < 0.05). Wistar caffeine rats had lower expression of c-Fos protein comparing to the Wistar control group only in SSCx. In CM, GAERS rats expressed lower c-Fos protein comparing to the Wistar control (p < 0.05). In conclusion differential effects of caffeine in the seizure modulation may involve c-Fos protein activity-dependent protection mechanisms.
Keywords: Pentylenetetrazole; GAERS; Caffeine; c-Fos protein; Thalamus; Somatosensorial cortex; GENETIC ABSENCE EPILEPSY; FOS MESSENGER-RNA; C-FOS; SOMATOSENSORY CORTEX; GABA(A) RECEPTOR; WAVE DISCHARGES; THALAMIC NUCLEI; EXPRESSION; RATS; SUSCEPTIBILITY